Respostas
respondido por:
1
a) (2a - 3)² = 4a² - 12a +9
b) 2p + 1/6 = 12p +1 / 6
c) (0,1 - x)² = 0,01 - 0,2x + x²
d) (3a+1)(3a-1) = 9a² - 1
Liliane
(a + b)² = a² + 2ab + b²
(a - b)² = a² - 2ab + b²
tenta fazer essa que vou deixar aqui :
( 2 + x)²
quem é a? quem é b?
a = 2
b = x
faz aí
e ( 2 - x)²
b) 2p + 1/6 = 12p +1 / 6
c) (0,1 - x)² = 0,01 - 0,2x + x²
d) (3a+1)(3a-1) = 9a² - 1
Liliane
(a + b)² = a² + 2ab + b²
(a - b)² = a² - 2ab + b²
tenta fazer essa que vou deixar aqui :
( 2 + x)²
quem é a? quem é b?
a = 2
b = x
faz aí
e ( 2 - x)²
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás